PENGARUH PROMOSI JABATAN TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BERINGIN LIFE - Ilyas, Ilyas (JGK (Jurnal Guru Kita), 2020)
Abstract: Effect of Job Promotion on Employee Performance at PT. Beringin Life. This study aims to determine the effect of Job Promotion on Employee Performance at PT. Banyan Life. The method used is explanatory research with a sample of 82 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable Job Promotion obtained an average score of 3.42 with good criteria. Employee Performance Variable obtained an average score of 3.78 with good criteria. Job Promotion has a positive and significant effect on Employee Job Performance with a regression equation value of Y = 11.691 + 0.773X, and a correlation coefficient value of 0.761 or has a strong level of relationship with a determination value of 57.9%. Hypothesis testing obtained a significance of 0.000